GENDER REPRESENTATION IN AN INDONESIAN GOVERNMENT-ENDORSED ENGLISH TEXTBOOK - Moh Irwansyah; Anandayu Suri Ardini (Wiralodra English Journal, 2023)
This study aims to identify the representation of gender in Indonesian government-endorsed English textbooks Specifically, the representation of gender in the textbook was essential because it depicted how society treats gender in a certain region. This study is based on a content-analysis investigation of gender representation in When English Rings the Bell SMP/MTs Kelas VII that the Indonesian government endorsed under the ministry of education. The whole data was collected through the instrument and was specified based on the need for gender representation that was made by Porrecca and was analyzed using Krippendorf's framework. This study reveals that man's representation was depicted as a strong character by depicting man as an outdoor worker with more choices of type of work. The woman's representation is depicted as a domestic worker, such as a chore. In addition, the male gender is represented as a masculine character, which is associated with types of nouns that were frequently associated with strength, wildness, and activeness, while the female gender was presented with typical nouns that were associated with beauty and passivity. The study still needs more exploration with other approaches to discover how gender is represented in the textbook.